Using smartphone step counts to monitor patients with total hip arthroplasty: The impact of patients’ living arrangements and residential location - Satoshi Yamate; Satoshi Hamai; Toshiki Konishi; Yuki Nakao; Takahiro Inoue; Goro Motomura; Yasuharu Nakashima (PLoS ONE, 2025)
Background Smartphone step counts may capture real-world activities in patients’ daily lives, and the self-monitoring of step counts may introduce healthier behavioral changes. We investigated the association between living arrangements (solitude/cohabiting) and residential location (urban/suburban) of patients and their preoperative and postoperative smartphone step counts following total hip arthroplasty (THA). Materials and methods Patients scheduled for THA at a university hospital from September 10, 2021, to December 5, 2023 were enrolled into the study from August 4, 2021, to November 10, 2023. We remotely monitored the patients’ daily step counts from smartphone application until up to 365 days after THA. We used the moving average method and latent growth curve modeling to analyze the time-series data of the step count. Results Overall, 85 patients were included in this study. Comparing the 37 solitary and 48 cohabiting patients, the percentage of men was higher in the solitary group (27% vs. 8%, P = 0.037). There were no notable differences in the demographics between the 44 urban and 41 suburban patients. Urban patients experienced a 483-step per 2-week greater preoperative increase than suburban patients (P = 0.027) after adjusting for confounding factors. From postoperative 2 weeks to preoperative 12 weeks, the intercept was larger for urban patients than for suburban patients by 893 steps (P = 0.040). From postoperative 20 weeks to preoperative 50 weeks, the intercept was larger for solitary patients than for cohabiting patients by a difference of 1,360 steps (P = 0.027). Conclusions Living arrangements and residential locations were associated with daily step counts before and after THA. Patients in urban areas had higher step counts after the initiation of step-count monitoring and during the early postoperative period. Solitary patients walked more than cohabiting patients. Our findings underscore the utility of smartphone step counts as objective outcome measures for patient assessment and encouraging healthier behavioral changes.